Screen time and its relationship with attention deficit hyperactivity disorder among children attending a tertiary care hospital - Ahmer, Zaeema; Sultan Dar, Marrium; Arif, Muriam; Shah, Mahjabeen; Ain, Noor ul; Habiba, Umme; Shahid, Fatima (Journal of the Pakistan Medical Association, 2023)
Objective: To estimate the frequency of attention deficit hyperactivity disorder and its relationship with screen time and sociodemographic characteristics among children. Method: The cross-sectional study was conducted at the National Institute of Child Health, Karachi, in June-July 2022, and comprised children of either gender aged 5-10 years visiting the paediatric outpatient department. Screen time was measured using a pretested questionnaire, while attention deficit hyperactivity disorder rating scale IV. The relationship of sociodemographic characteristics and screen time with the disorder was explored through multiple linear regression analysis. Data was analysed using SPSS 20. Results: Of the 247 participants, 126(51%) were boys and 121(49%) were girls. The overall mean age was 7.84 ±1.87 years. The were 149(60.3%) children at the primary level of education, while 76(30.8%) had no formal education. There were 139(56.3%) children having screen time >2 hours/day with a mean of 3.36±3.14 hours. There were 15(6.1%) children with attention deficit hyperactivity disorder score >26 with a mean of 11.58±9.27. Boys were more frequently affected by attention deficit hyperactivity disorder compared to girls (p=0.026), and there was a significant positive correlation between screen time and attention deficit hyperactivity disorder (p<0.001). Conclusion: The majority of children were found to be spending more than the recommended time on screen. Male gender and screen time were associated with attention deficit hyperactivity disorder. Key Words: Screen time, Attention deficit hyperactivity disorder, Child.